Dyslipidaemia and its underlying mechanisms in coronavirus disease 2019 (COVID-19) infection - Hamad Zubi, Zainab Bubakr; Hamad Alfarisi, Hamad Abdulsalam (Science Publishing Group, 2023)
Dyslipidaemia is a biochemical alteration connected to the pathology accompanying COVID-19 infection. Dyslipidaemia has been recognized as a common complication in COVID-19 infection exerting a significant effect on severity and mortality in COVID-19 infected patients. Disturbance of lipid profile in COVID-19 infection is diverse and shown to have various presentations. Inflammatory markers and acute phase reactants found to have a relation with the disrupted lipid profile during COVID-19 infection. The objective of this short review is to outline the altered lipid profile in COVID-19 infected patient, and to highlight the relationship between dyslipidaemia, inflammatory markers, severity and morbidity of COVID infection. The implemented methodology in this comprehensive short review is based on analysis of the recent published literature pertaining dyslipidaemia in COVID-19 infection. The core literature for this review is the published clinical studies and the case reports that studied the effects of COVID-19 infection on lipid profile. This review showed that low total cholesterol and high-density lipoprotein cholesterol (HDL-C) in addition to elevated low-density lipoprotein cholesterol (LDL-C) constitute the commonest altered lipid profile in COVID-19 infected patients. Lipid peroxidation, oxidative stress and inflammation are the postulated pathogenic mechanisms for dyslipidaemia during COVID-19 infection. However, the results about status of triglycerides (TG) in COVID-19 infection was non-conclusive. Further studies may be required to suite the lipidomic status of triglycerides in COVID-19 infected patients.